Handschinurida nom. nov. (Collembola, Neanuridae), a substitute name for the homonym Handschinia Stach, 1949 - Queiroz, Gabriel Costa (Zootaxa, 2015)
Stach (1949) erected the genus Handschinia Stach, 1949 (Collembola, Neanuridae, Pseudachorutinae sensu Deharveng, 2004) for two Neotropical species, Pseudachorutes fluminensis Arlé, 1939 and Pseudachorutes proximus Arlé, 1939. Later, Massoud (1967) synonymised the genus with Arlesia Handschin, 1942. More recently, Queiroz & Mendonça (2014) rediagnosed Handschinia Stach, 1949 as a valid genus based on new morphological characteristics regarding the two mentioned species and also the description of Handschinia rauli Queiroz & Mendonça, 2014. It was not recognised by Queiroz & Mendonça (2014) that Ellis & Bellinger (1973) had already that Handschinia Stach, 1949 as a junior homonym of Handschinia Lallemand, 1935, a hemipteran genus. Ellis & Bellinger (1973) refrained from creating a replacement name because Handschinia Stach, 1949 had been synonymised with Arlesia, that had priority if the synonymy was valid.